2012
DOI: 10.1016/j.ajog.2011.08.026
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal cuff dehiscence: risk factors and management

Abstract: Vaginal cuff dehiscence and evisceration are rare but serious complications of pelvic surgery, specifically hysterectomy. The data on risks of vaginal cuff dehiscence are variable and there is no consensus on how to manage this complication. In our review, we present a summary of the risk factors, presenting symptoms, precipitating events, and management options for patients who present with vaginal cuff dehiscence after pelvic surgery. In addition, we provide a review of the current literature on this importa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
137
2
8

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(148 citation statements)
references
References 43 publications
1
137
2
8
Order By: Relevance
“…4,5,10 Both laparoscopic and, in particular, robotic-assisted laparoscopic hysterectomies were associated with higher odds of dehiscence. These findings correlate with the available literature 1,12,13 and may reflect the accumulation of more experience with laparoscopic hysterectomy than with robotic-assisted hysterectomy at our institution.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…4,5,10 Both laparoscopic and, in particular, robotic-assisted laparoscopic hysterectomies were associated with higher odds of dehiscence. These findings correlate with the available literature 1,12,13 and may reflect the accumulation of more experience with laparoscopic hysterectomy than with robotic-assisted hysterectomy at our institution.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of this condition as reported in the literature is 0% to 7% and appears to be higher after laparoscopic and robotic approaches compared with vaginal and abdominal approaches. [1][2][3][4][5] Uccella et al 1 previously reported the incidence to be 0.13% when the procedure is performed by the vaginal approach, 0.2% when performed abdominally, and 0.64% when performed by the laparoscopic approach. Risk factors are ill-defined 5 and include factors that influence wound healing, as well as mechanical factors such as early resumption of sexual activity, trauma, and increased intra-abdominal pressure.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bu nedenle daha az hemostazı yapılmış bir vajinal kaf, sıfır kanamalı kuru bir vajinal kaf tercih edilmelidir (12). herhangi bir histerektomiden sonra kaf dehisensi %0,14-4,1 oranlarında görüle-bilirken, vajinal kafın vajinal yoldan kapatılması dehisens riskini 3 ile 9 kat oranında azaltmaktadır (13,14). ayrıca son zamanlarda tek yönlü gömülen dikişlerin kullanıldığı robotik olgularda vajinal kaf dehisensinin dramatik bir şekilde azaldığı gösterilmiştir (15 (5,6).…”
unclassified